Complete remission in metastatic hepatocellular carcinoma. Issue 3 (28th February 2023) - Ben Kridis, Wala; Kallel, Rim; Boudawara, Tahia; Khanfir, Afef
Abstract: Bone metastases from hepatocellular carcinoma (HCC) are unusual. Optimal treatment strategies are not well defined. The prognosis of this entity is very poor with a survival that does not exceed 1 year. We report here a new case of metastatic HCC with longer overall survival of more than 5 years in a 67‐year‐old man. Abstract : We report here a new case of metastatic hepatocellular carcinoma with longer overall survival of more than 5 years in a 67‐year‐old man.